2012
DOI: 10.1126/scitranslmed.3004504
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Subtypes and Large-Scale Epigenetic Alterations in Gastric Cancer

Abstract: Epigenetic alterations are fundamental hallmarks of cancer genomes. We surveyed the landscape of DNA methylation alterations in gastric cancer by analyzing genome-wide CG dinucleotide (CpG) methylation profiles of 240 gastric cancers (203 tumors and 37 cell lines) and 94 matched normal gastric tissues. Cancer-specific epigenetic alterations were observed in 44% of CpGs, comprising both tumor hyper- and hypomethylation. Twenty-five percent of the methylation alterations were significantly associated with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 52 publications
6
141
0
Order By: Relevance
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…Tumour suppressor genes such as CDH1 and RUNX3 are often silenced in primary GCs by promoter DNA methylation 12,13 , and changes in DNA methylation have also been associated with GC prognosis, chemosensitivity and drug resistance [14][15][16] . More recently, genome-wide studies have highlighted a role for both global and non-CpG island methylation in specific GC subtypes [17][18][19] , and exomesequencing studies have revealed that genes involved in chromatin modification such as ARID1A are frequently mutated in GC 2,4 . Currently however, the vast majority of epigenetic studies in GC have focused on characterizing patterns of aberrant DNA methylation.…”
mentioning
confidence: 99%
“…Our data suggested a link between higher DNA methylation levels prior to decitabine treatment and better sensitivity to HMAs. In gastric cancers, Zouridis et al 36 reported the association of the CpG island methylator phenotype (CIMP) with better sensitivity to DNA methylation inhibitors. CIMP tumor type was identified in 68 of 203 primary gastric tumors and 7 of 17 gastric cancer cell lines, which displayed a unique feature of widespread hypermethylation at a global level compared to non-CIMP tumor type.…”
Section: Discussionmentioning
confidence: 99%